Aspects of the cosmic Christ in the spirituality of Dom Bede Griffiths - Forster, Dion Angus (Rhodes University, Faculty of Divinity, Department of Divinity, 2001)
Alan Griffiths was born at Walton-on Thames, England in 1906. He was educated at Christ's Hospital and later at Oxford (under the tutelage of C.S. Lewis). At Oxford he read English literature and philosophy. After considerable inner turmoil he was converted to Christianity in 1931 and entered the Roman Catholic Church in 1933. As a novice Benedictine he was given the name Bede, and was finally ordained as a priest 1940. In 1955 Fr Bede went to India to start a Benedictine community with Dom Benedict Alapatt. He later moved to Kurisumala Ashram in Kerala, and finally, in 1968, to Shantivanam Ashram in Tamil Nadu. He died at Shantivanarn in 1993. Fr Bede was, and still is, regarded by many as a spiritual pioneer. This high regard stems from an appreciation of his spirituality which was rooted in a mystical experience of God. This thesis investigates aspects of Fr Bede's cosmic christology as they arise from his spirituality. The aim of this research is to show that Fr Bede's cosmic christology that stems from an expression of a real mystical experience of Christ, as the source, sustainer and goal of the whole cosmos, offers both value and insight to Christian spiritual practice and the formulation of doctrine. What makes Fr Bede's spirituality so valuable is the manner in which he integrated East and West in his spirituality and person, coupled with his ability to draw upon that integration in reflecting and articulating his experience - which ultimately shaped his cosmic christology. In order to share his knowledge and experience of the cosmic Christ, Fr Bede draws upon linguistic and philosophical concepts from the East (and Hinduism in particular) as well as the language and theory arising from discoveries in the areas of quantum physics, microbiology and transpersonal psychology in the West. It is the primacy of spiritual experience, coupled with Fr Bede's ability to integrate the religions, cultures and world-views of the East and West within himself, which makes his cosmic christology so compelling.
Keywords: Griffiths, Bede, 1906-1993; Catholic Church -- India -- Clergy -- Biography